SENI: ANTARA BENTUK DAN ISI - Widyabakti Sabatari (FBS UNY, 2006)
When a new art work is created, it usually causes the emergence ofnew definitions of art, which are based on different points of view andinterpretations. Therefore, it is difficult to give an ideal definition of art. Thescope of art is so wide and the facet is so various that art has plural meanings.There are always incomplete and incomprehensive views of art. There are alsomany different branches of art. On account of its wide scope, the philosophyof art is badly needed as a way to comprehend and analyze matters related toart and its definitions.Based on a view that there is no difference between art and beauty,every beautiful thing is an art and on the contrary something that has thevalues of art is certainly beautiful. This view causes overlapping descriptionsof art meanings. Accordingly, art and beauty often replace each other in theworld of art. The question is then about the meaning of art and of beauty, andits forms and shapes.To create an art work, it is impossible to neglect materials that formit. An art work is physical but the shape itself is not necessarily regarded asart. Whether a physical shape has art values depends on the values inside.These inner values, the so-called art content values, are the first to catch by artappreciators and lovers. In comprehending an art work, the Forms of FashionBase and the Form and Content in the Fashion Work is applicable to analysean art's form and conent.Key words: art, form and content